SAE 1064, SAE 1065, ISO CS65, JIS S65CM, JIS S65C, JIS S65C-CSP (Alloy Digest, 2025)
Abstract 1064, 1065, CS65, S65CM, S65C, and S65C-CSP are wrought high-carbon non-alloy steels that are typically used in the cold reduced, patented and cold drawn, quenched and tempered, or austempered condition. These steels are widely used for highly stressed parts that require higher strength levels than can be achieved with lower carbon grades. They are also used for applications where the higher carbon is needed to improve wear characteristics. This datasheet provides information on composition, physical properties, microstructure, hardness, and tensile properties. It also includes information on high temperature performance as well as forming and heat treating. Filing Code: CS-270. Producer or source: Heat Treater’s Guide Data Sheet.